Clinical and molecular characterization of five Chinese patients with autosomal recessive osteopetrosis. Issue 11 (21st September 2021) - Liang, Huanhuan; Li, Niu; Yao, Ru‐en; Yu, Tingting; Ding, Lixia; Chen, Jing; Wang, Jian
Abstract: Background: Osteopetrosis is characterized by increased bone density and bone marrow cavity stenosis due to a decrease in the number of osteoclasts or the dysfunction of their differentiation and absorption properties usually caused by biallelic variants of the TCIRG1 and CLCN7 genes. Methods: In this study, we describe five Chinese children who presented with anemia, thrombocytopenia, hepatosplenomegaly, repeated infections, and increased bone density. Whole‐exome sequencing identified five compound heterozygous variants of the CLCN7 and TCIRG1 genes in these patients. Results: Patient 1 had a novel variant c.1555C>T (p.L519F) and a previously reported pathogenic variant c.2299C>T (p.R767W) in CLCN7 . Patient 2 harbored a novel missense variant (c.1025T>C; p.L342P) and a novel splicing variant (c.286‐9G>A) in CLCN7 . Patients 3A and 3B from one family displayed the same compound heterozygous TCIRG1 variant, including a novel frameshift variant (c.1370del; p.T457Tfs*71) and a novel splicing variant (c.1554+2T>C). In Patient 4, two novel variants were identified in the TCIRG1 gene: c.676G>T; p.E226* and c.1191del; p.P398Sfs*5. Patient 5 harbored two known pathogenic variants, c.909C>A (p.Y303*) and c.2008C>T (p.R670*), in TCIRG1 . Analysis of the products obtained from the reverse transcription‐polymerase chain reaction revealed that the c.286‐9G>A variant in CLCN7 of patient 2 leads to intron 3 retention, resulting in the formation of a premature termination codon (p.E95Vfs*8). These five patients were eventually diagnosed with autosomal recessive osteopetrosis, and the three children with TCIRG1 variants received hematopoietic stem cell transplantation. Conclusions: Our results expand the spectrum of variation of genes related to osteopetrosis and deepen the understanding of the relationship between the genotype and clinical characteristics of osteopetrosis. Abstract : Biallelic variants in TCIRG1 and CLCN7 are responsible for Chinese ARO patients. Seven novel variants in TCIRG1 and CLCN7 were identified in Chinese ARO patients. The novel variants c.286‐9G>A in CLCN7 leads to intron 3 retention.